Tidal analysis at Kuala Langsa and Pusong Island using Admiralty method - ANNISA S. SUGIARTI; . MARWAN; ICHSAN SETIAWAN (Syiah Kuala University, 2014)
A research about tidal analysis at Kuala Langsa and Pusong Island with different physical condition had been done, where Kuala Langsa is an estuary and Pusong Island is a coastal area in Kota Langsa District, Aceh Province. The purpose of this research is to determine tidal type on both locations. This research used secondary data which is obtained from Kuala Langsa – Pusong Island Hydro – Oceanographic Survey and primary data which is taken about 29 hours at both locations. Admiralty method had been using to analyze the tides and from this method can be obtain amplitude and phase lag based on Formhazl number. The result of this research according to Formhazl number for Kuala Langsa and Pusong Island are 0.12 and 0.23 respectively. Both values of Formhazl number of the locations are smaller than 0.25, it concluded that both locations had showed same tidal type, i.e. semidiurnal. The phase lag for tidal types in Kuala Langsa for M2 is 3590while for Pusong Island is 3300. While for the amplitude of both locations for M2 is 56 cm for Kuala Langsa and 48 cm for Pusong Island. It is shown that the amplitudes at Kuala Langsa are a little bit higher than that of Pusong Island. The difference is suspect due to the different physical condition of the observation areas